The Evolution of the Open Textbook Initiative. Issue 2 (3rd April 2021) - Ponte, Frank; Lennox, Anne; Hurley, Jennifer
ABSTRACT: In 2018, RMIT University Library was awarded 5, 000 fellowship from Libraries of the Australasian Network (LATN) to investigate opportunities in open educational resources (OER). The reasons behind the application were to advocate and increase the use of OER, increase knowledge and expertise in open licencing, and leverage support, advice and appropriate infrastructure from LATN members. The associated benefits to LATN would include the establishment of an OER community of practice and the development of shared tools and resources to facilitate the uptake of open educational resources at home institutions. This is the story of how the Open Textbook Initiative evolved and how a deliberate campaign to increase awareness and adoption of OER was created. Activities included delivering OER awareness sessions, aligning OER textbooks with selected subject areas, delivering an open textbook forum, with local and international speakers, and creating a savings bank for self-reported OER adoptions. The OER textbook hero program was developed to highlight the teaching challenges faced by academic staff and explore their responses. As a result of this activity, there has been greater visibility of OER and the discussion has evolved from textbook affordability to open educational practices.